THE ROLE OF THE SOUTH HALMAHERA REGENCY INDUSTRY AND TRADE DEPARTMENT IN THE SALE OF THRIFTING GOODS - Dahlai Hasim; Mardia Ibrahim; Muhammad Amin Hanafi; Arief Budiono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study examines the widespread sale of imported used clothing (thrift trade) in South Halmahera Regency. The research is driven by concerns that the importation and trade of used clothing contradict existing laws and may pose health risks to consumers. The study aims to analyze the legal framework governing the imported used clothing trade and to identify the efforts undertaken by the South Halmahera Department of Trade and Industry to address the issue. Using an empirical normative legal method, the research relies on primary data gathered through observations and interviews. The findings reveal the absence of specific regional regulations controlling the entry of used clothing into North Maluku Province, allowing such goods to be traded freely. In response, the Department of Trade and Industry has implemented measures such as organizing sales locations and coordinating with the provincial government to strengthen regulation at the import level. The study highlights Ministerial Regulation No. 40 of 2022, which prohibits the import of used goods, including used clothing. Additionally, the research notes that Indonesia’s main suppliers of used clothing in 2023 were the UK, Taiwan, and Hong Kong.